Utilization of Digital Media in Managing Mental Health of Educational Technology Students at Ibn Khaldun University Bogor - Rudi Hartono; Alfira Ajrin; Suci Sabila Noer; Nadya Nurfirmansyah (CV. Media Inti Teknologi, 2024)
The purpose of this study is to better understand how students enrolled in the Education Technology Study Program at Ibn Khaldun University of Bogor use digital media to manage their mental health. Descriptive qualitative research methodologies were used in this study, and data was gathered through interviews. 84 respondents, who were Ibn Khaldun University of Bogor students studying educational technology in semesters 1, 3, 5, and 7, participated in this survey. The findings of this study suggest that students enrolled in the Educational Technology Study Program at Ibn Khaldun University of Bogor may have difficulties managing their mental health as a result of digital media. Student responses made during interviews make it clear that digital media can improve awareness and comprehension of mental health management. The study's conclusion is that students in Ibn Khaldun University of Bogor's Education Technology Study Program have significant mental health effects from digital media. It is therefore envisaged that students will be able to focus more on how digital media is used to manage mental health.